Boom, slump, sudden stops, recovery, and policy options: Portugal and the Euro - Olivier Blanchard; Pedro Portugal (Institute of Labor Economics (IZA), 2017)
Over the past 20 years, Portugal has gone through a boom, a slump, a sudden stop, and now a timid recovery. Unemployment has decreased, but remains high, and output is still far below potential. Competitiveness has improved, but more is needed to keep the current account in check as the economy recovers. Private and public debt are high, both legacies of the boom, the slump and the sudden stop. Productivity growth remains low. Because of high debt and low growth, the recovery remains fragile. We review the history and the main mechanisms at work. We then review a number of policy options, from fiscal consolidation to fiscal expansion, cleaning up of non-performing loans, labor market reforms, product market reforms, and euro exit. We argue that at this point, the main focus of macroeconomic policy should be twofold. The first is the treatment of non- performing loans, which would allow for an increase in demand in the short run and an increase in supply in the medium run. We argue that, to the extent that such treatment requires recapitalization, it makes sense to finance it through an increased fiscal deficit, even in the face of high public debt. The second is product market reforms, and reforms aimed at increasing micro-flexibility in the labor market. Symmetrically, we also argue that at this point, some policies would be undesirable, among them faster fiscal consolidation, measures aimed at decreasing nominal wages and prices, and euro exit.
Keywords: E32; E62; J30; J60; 330; competitiveness; debt; productivity growth; structural reforms